The Loyalty of K-Pop Fans Enhances the Innovation of Internationally Competitive Souvenirs for Small and Medium Sized Enterprises (SMES) : (A Case Study on Zonnebloem Souvenir) - Restu Millaningtyas; Sudarmiatin Sudarmiatin (Pusat Riset dan Inovasi Nasional, 2025)
The K-Pop music industry has experienced tremendous growth and emerged as a global phenomenon, impacting other sectors, including the souvenir industry. The allegiance of devoted K-Pop enthusiasts significantly influences the purchase of memorabilia associated with their heroes. K-Pop memorabilia serves not merely as commodities, but also as emblems of cultural identity for enthusiasts. Consequently, SMEs involved in souvenir production possess significant potential to enhance the competitiveness of their products in both home and international markets. This study seeks to examine the influence of K-Pop fan devotion on the competitiveness of souvenir products and to identify business strategies that SMEs, like Zonnebloem Souvenir, can implement to compete in the worldwide market. Employing qualitative methodologies alongside the Business Model Canvas (BMC) and SWOT analysis to assess the business model of Zonnebloem Souvenir. Data was collected by observation, interviews, and documentation, then analyzed to formulate a business development strategy. The data indicates that Zonnebloem Souvenir has effectively leveraged K-Pop fan loyalty via product innovation and digital marketing, enabling international marketability. Zonnebloem enhances competitiveness by diversifying distribution channels, elevating product quality, and perpetually innovating in response to the burgeoning K-Pop trends in the global market.